PENGARUH EKSTRAK BUNGA TELANG (Clitoria ternatea) TERHADAP Escherichia coli DAN Staphylococcus aureus - Dina Trianggaluh Fauziah (Yayasan Pendidikan Medika Indonesia, 2022)
Abstract Telang flower is a plant also known as flower telang which contains saponins, alkaloids, flavonoids, triterpenoids and phenols which function as laxative, diuretic, blood purifier and anthelmintic. This study aims to determine the effect of telang flower on antibacterial test. The extraction method used is maceration and soxhletation, the yield obtained by maceration (1.40%) and soxhletation (2.15%) methods. The average inhibitory power of telang flower extract on the antibacterial test of Escherichia coli on the maceration method (11.6 mm) and the soxhletation method (12.6 mm), while the antibacterial testing of Staphylococcus aureus with the maceration method (13.3 mm) and soxhletation (10,6 mm). Qualitative identification showed the presence of alkaloids, tannins and saponins.